1974
DOI: 10.1083/jcb.60.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Migration, and Release of Precursor Collagen by Odontoblasts as Visualized by Radioautography After [3h]proline Administration

Abstract: The elaboration of dentin collagen precursors by the odontoblasts in the incisor teeth of 30-40-g rats was investigated by electron microscopy, histochemistry, and radioautography after intravenous injection of tritium-labeled proline .At 2 min after injection, when the labeling of blood proline was high, radioactivity was restricted to the rough endoplasmic reticulum, indicating that it is the site of synthesis of the polypeptide precursors of collagen, the pro-alpha chains .At 10 min, when the labeling of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
159
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(178 citation statements)
references
References 64 publications
18
159
1
Order By: Relevance
“…Labeled amine acids are essentially c1eared from the b100d plasma by 1 ho ur after intravenous injection (Nakagami et al, 1971). Weinstock and Leblond (1974) found that the amount of free labe1ed proline in the b100d plasma dropped sharp1y during the first 10 minutes after injection and concluded that a pulse of high raclioactivity was achieved. However, a 10w but significant level of radiol activity pers isted between 30 minutes and 30 hours after injection.…”
Section: Response Of the Enamel Organ And Ename! To Drilling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeled amine acids are essentially c1eared from the b100d plasma by 1 ho ur after intravenous injection (Nakagami et al, 1971). Weinstock and Leblond (1974) found that the amount of free labe1ed proline in the b100d plasma dropped sharp1y during the first 10 minutes after injection and concluded that a pulse of high raclioactivity was achieved. However, a 10w but significant level of radiol activity pers isted between 30 minutes and 30 hours after injection.…”
Section: Response Of the Enamel Organ And Ename! To Drilling Proceduresmentioning
confidence: 99%
“…In bone and dent ln, some of the secreted proteins become part of a collageno~s uatrix which 18 transformed into mineralized products of the cells (Carneiro and Leb1ond.' 1959;Young and Greulich, 1963;Weinstock and Leblond, 1974).…”
Section: Response Of the Enamel Organ And Ename! To Drilling Proceduresmentioning
confidence: 99%
“…However, quantitative electron microscope autoradiographic studies gave conflicting results as to the amount of proline-rich protein passing from endoplasmic reticulum into the Golgi vacuoles of THE JOURNAL OF CELL BIOLOGY • VOLUME 65, 1975 • pages 75-87several cell types (12,27,28,34) and suggested that two intracellular pathways might exist for collagen transport (27,28).…”
mentioning
confidence: 99%
“…Procollagen is unusual insofar as it is secreted by several distinct cell types. In fact, morphological differences in the extent and character of the Golgi apparatus among collagen-secreting cells may be part of the basis for the different interpretations regarding the mode(s) of intracellular transport and secretion of this protein (12,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation